DHHC2 regulates fear memory formation, LTP, and AKAP150 signaling in the hippocampus - Meng-Die Li; Lu Wang; Yu-Qi Zheng; Dan-Hong Huang; Zhi-Xuan Xia; Jian-Min Liu; Dan Tian; Hui OuYang; Zi-Hao Wang; Zhen Huang; Xiao-Shan Lin; Xiao-Qian Zhu; et al. (iScience, 2023)
Summary: Palmitoyl acyltransferases (PATs) have been suggested to be involved in learning and memory. However, the underlying mechanisms have not yet been fully elucidated. Here, we found that the activity of DHHC2 was upregulated in the hippocampus after fear conditioning, and DHHC2 knockdown impaired fear induced memory and long-term potentiation (LTP). Additionally, the activity of DHHC2 and its synaptic expression were increased after high frequency stimulation (HFS) or glycine treatment. Importantly, fear learning selectively augmented the palmitoylation level of AKAP150, not PSD-95, and this effect was abolished by DHHC2 knockdown. Furthermore, 2-bromopalmitic acid (2-BP), a palmitoylation inhibitor, attenuated the increased palmitoylation level of AKAP150 and the interaction between AKAP150 and PSD-95 induced by HFS. Lastly, DHHC2 knockdown reduced the phosphorylation level of GluA1 at Ser845, and also induced an impairment of LTP in the hippocampus. Our results suggest that DHHC2 plays a critical role in regulating fear memory via AKAP150 signaling.